Search for Yield in Large International Corporate Bonds : Investor Behavior and Firm Responses - Calomiris, Charles W. (World Bank, Washington, DC, 2019)
Emerging market corporations have significantly increased their borrowing in international markets since 2008. This paper shows that this increase was driven by large-denomination bond issuances, most of them with face value of US$500 million. Large issuances are eligible for inclusion in international market indexes, which attract institutional investors. Emerging market firms were able to cut their cost of funds by roughly 100 basis points by issuing large-denomination bonds. Firms face a tradeoff: issue large, index-eligible bonds to borrow at a lower cost (about 100 basis points) but pay the expense of hoarding cash. Because of the "size yield discount," many companies issued index-eligible bonds, increasing their cash holdings. The willingness to issue large bonds and hoard cash was greater for firms in countries with high carry trade opportunities. These post-2008 behaviors reflected a search for yield by institutional investors into higher-risk securities and are not apparent in developed economies.